Homeostasis and metabolism of iron and other metal ions in neurodegenerative diseases - Leilei Chen; Qingqing Shen; Yingjuan Liu; Yunqi Zhang; Liping Sun; Xizhen Ma; Ning Song; Junxia Xie (Signal Transduction and Targeted Therapy)
Abstract As essential micronutrients, metal ions such as iron, manganese, copper, and zinc, are required for a wide range of physiological processes in the brain. However, an imbalance in metal ions, whether excessive or insufficient, is detrimental and can contribute to neuronal death through oxidative stress, ferroptosis, cuproptosis, cell senescence, or neuroinflammation. These processes have been found to be involved in the pathological mechanisms of neurodegenerative diseases. In this review, the research history and milestone events of studying metal ions, including iron, manganese, copper, and zinc in neurodegenerative diseases such as Parkinson’s disease (PD), Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD), will be introduced. Then, the upstream regulators, downstream effector, and crosstalk of mental ions under both physiologic and pathologic conditions will be summarized. Finally, the therapeutic effects of metal ion chelators, such as clioquinol, quercetin, curcumin, coumarin, and their derivatives for the treatment of neurodegenerative diseases will be discussed. Additionally, the promising results and limitations observed in clinical trials of these metal ion chelators will also be addressed. This review will not only provide a comprehensive understanding of the role of metal ions in disease development but also offer perspectives on their modulation for the prevention or treatment of neurodegenerative diseases.